2021
DOI: 10.1177/1461444820929321
|View full text |Cite
|
Sign up to set email alerts
|

Future imaginaries in the making and governing of digital technology: Multiple, contested, commodified

Abstract: Visions of the future are omnipresent in current debates about the digital transformation. This introductory article and the full special issue are concerned with the function, power, and performativity of future visions and how they relate to the making and governing of digital technology. Revisiting existing concepts, we particularly discuss and advance the concept of sociotechnical imaginaries. In difference to ephemeral visions and partisan ideas, imaginaries are collectively held and institutionally stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…These moments of contemplative friction are needed in a world where future imaginaries around digital technologies, its making and its governance, are increasingly dominated by technology companies that 'partly absorb public institutions' ability to govern these very futures with their rhetoric, technologies and business models' (Mager and Katzenbach, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These moments of contemplative friction are needed in a world where future imaginaries around digital technologies, its making and its governance, are increasingly dominated by technology companies that 'partly absorb public institutions' ability to govern these very futures with their rhetoric, technologies and business models' (Mager and Katzenbach, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a disconnect between commercially driven sales narratives (or 'socio-technical imaginaries') and actual technological capabilities. The increasinginfluenceofthesecorporateimaginariesonsocietyandpolicymayhavesignificantimplicationsforcitizens and the ability of counter-imaginaries to gain traction (Mager and Katzenbach, 2020).…”
Section: Characteristics Of Geno-digital Sporesmentioning
confidence: 99%
“…In recent years, Science and Technology Studies (STS) has increasingly become interested in the conjunction of discourse and the making of politics and technology (Mager and Katzenbach 2021). Scholars study "expectations and stories about the future" (van Lente and Rip 1998; van Lente 2016), the role of technological innovations, and visionary rhetoric in enterprises (Beckert 2016) and highlight the discursive struggles around "contested futures" (Brown, Rappert, and Webster 2017).…”
Section: Conceptual Frame: Sociotechnical Imaginaries (Sis) Myths and The Sublimementioning
confidence: 99%
“…The authors assert that sustaining imaginaries are always "associated with active exercises of state power, such as the selection of development priorities, the allocation of funds, the investment in material infrastructures" (Jasanoff and Kim 2009, 123). While subsequent research has shown that imaginaries are routinely rather multiple, contested, and commodified than uniform visions of the state (Mager and Katzenbach 2021;Jasanoff 2015), the role of the state remains crucial. It has the capacity to structure future expectations by combining powerful measures of issuing regulations and allocating resources with its own narratives and visions.…”
Section: Conceptual Frame: Sociotechnical Imaginaries (Sis) Myths and The Sublimementioning
confidence: 99%
“…Promising to make life easier, to mimic human intelligence and surpass it, aspirational rhetorics around AI silence critics by promising that any shortfalls will be solved in the future (Floridi, 2020). The sociotechnical imaginaries surrounding AI (Jasanoff and Kim, 2009) are multiple and powerful, though increasingly commodified by vendors to generate what has recently been termed the 'corporate sociotechnical imaginary' (Hockenhull and Cohn, 2021;Mager and Katzenbach, 2021). From this perspective, vendors and other industry actors generate visions of the future full of effective and ubiquitous AI services as a mechanism to generate increased funding (Mu¨tzel, 2021).…”
Section: Ai-as-a-servicementioning
confidence: 99%